198k views
3 votes
{[9+3) divided by 2] - 2} times [3 times (14 - 5)] =

2 Answers

3 votes

Answer:

Solve the numbers in the brackets first

9+3 = 12

12/2 = 6

14-5 = 9

9 × 3 = 27

Take the answers got from the two brackets and multiply them together

6×27 = 162

User George Co
by
4.6k points
6 votes

Answer:

Explanation:

Use PEDMAS

First the inner parenthesis

i) (9+3) & (14-5)

ii) [12 ÷ 2] & [3*9]

iii) {6- 2}

{[(9 + 3) ÷ 2] - 2} * [3*(14 - 5)]={[12 ÷ 2] - 2} * [3*9]

= {6-2}* [27]

= 4 * 27

= 108

User Sven Liivak
by
4.7k points